Population Mechanisms of Risk of Development of Cholelithiasis, Algorithms of Early Diagnosis, Prevention and Optimization of its Treatment Among the Population of the Fergana Valley of the Gerontological Group - Mamasaliev N. S.; Salakhidinov S. Z.; Mamasaliev Z. N.; Olimova N. A. (Scientific Trends, 2025)
The article presents modern, foreign and domestic data on the problem of epidemiology, prevention and treatment of cholelithiasis (gallstone disease). The analysis of population studies and preventive programs forcholelithiasisin the population of the gerontological and geriatric group is carried out. The article discusses modern recommendations for the use of screening, various types of preventive studies, conservative and surgical methods of treatment of cholelithiasis.
Keywords: Cholelithiasis, epidemiology, prevention, pharmaco-epidemiology, risk factors, geriatric features of early detection and treatment of cholelithiasis.